Camrelizumab combined with anlotinib as second-line therapy for metastatic or recurrent small cell lung cancer: a retrospective cohort study - Shen, Shujing; Li, Xingya; Guo, Sanxing; Xu, Liang; Yan, Ningning (Frontiers in Oncology, 2024)
Introduction This retrospective study evaluates the efficacy of camrelizumab combined with anlotinib versus chemotherapy in patients with extensive-stage small-cell lung cancer (ES-SCLC) undergoing second-line treatment. Methods Data were sourced from medical records at a Chinese medical facility, involving 34 patients diagnosed with ES-SCLC after failing first-line treatment. Patients were divided into two groups: one received camrelizumab (200 mg every 3 weeks) with anlotinib (12 mg daily for 14 days followed by a 7-day rest), while the other group received physician-chosen chemotherapy administered every 3 weeks. The primary endpoint was progression-free survival (PFS), with secondary endpoints including overall survival (OS), objective response rate (ORR), and disease control rate (DCR). Results The combination therapy group showed a significant improvement in PFS compared to the chemotherapy group (median PFS: 7 months vs. 3 months; hazard ratio (HR): 0.34; 95% confidence interval (CI): 0.15-0.77; p<0.001). However, there was no statistically significant difference in OS between the groups (16.3 months vs. 17.3 months; p=0.82). The ORR was 52.9% in the combination therapy group versus 23.5% in the chemotherapy group (p=0.08), and the DCR was 82.4% compared to 58.8% (p=0.26). Grade 3 or higher adverse events were observed in 17.6% of the combination therapy group and 29.4% of the chemotherapy group. Conclusions The findings suggest that the combination of camrelizumab and anlotinib offers a superior anti-tumor response with a manageable safety profile in a second-line setting for ES-SCLC patients. This combination regimen may be a viable option for second-line ES-SCLC treatment.